Environmental Protection – Shifting the Focus toward the Protected Object - Cvetić, Radenka Milorad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
This article is an attempt to provide a comprehensive overview of the rationale which led to developments in the law of environmental protection in a direction of an even more efficient protection of environment from human beings. There has been a transformation of the constitutionally protected right to a healthy environment to the Constitutional guarantee which involves both duty and responsibility for its protection. There has also been a shift from declaratory protection toward enforceable prohibitions and orders. These transformations have occurred when the society faced, under dramatic circumstances, the situation which shows that failure to protect the common good could lead to catastrophic consequences. The system of environmental protection, which enables sustainable development, is based on the primacy of the precautionary principle which deals with prevention and reduction of probability of harm, as well as on the no fault liability of the polluter for the environmental harm even in the absence of the claim for damages. The efficacy of the environmental protection could be improved by raising the awareness of the preservation of environment. The understanding that the protection of environment amounts to a survival of a mankind could lead to creating rights for the environment as such.
Keywords: environmental damage; preventive and precautionary principle; duties; rights; environment; liability